(untitled) (Global Journal of Science Frontier Research, 2017)
This study examined the awareness level and attitude of family planning among rural dwellers in the South western part of Nigeria and its consequences on population/economy of Nigeria. Data were gathered from 300 respondents who were randomly selected from Seriki rural communities of western Nigeria using proportional allocation of the stratified random sampling technique. The research considered to know the level of awareness between the traditional family planning methods and modern methods of contraception. The modern methodswere found to be more significantly embraced than traditional family planning methods based on the analysis of the result obtained which shows that 175% prefer modern methods while 125% preferred traditional methods.